Application of Monte Carlo simulations to uncertainty assessment of ship powering prediction by the 1978 ITTC method - Seo, Jeonghwa; Park, Jongyeol; Go, Seok Cheon; Rhee, Shin Hyung; Yoo, Jaehoon (International journal of naval architecture and ocean engineering, 2021)
The present study concerns uncertainty assessment of powering prediction from towing tank model tests, suggested by the International Towing Tank Conference (ITTC). The systematic uncertainty of towing tank tests was estimated by allowance of test setup and measurement accuracy of ITTC. The random uncertainty was varied from 0 to 8% of the measurement. Randomly generated inputs of test conditions and measurement data sets under systematic and random uncertainty are used to statistically analyze resistance and propulsive performance parameters at the full scale. The error propagation through an extrapolation procedure is investigated in terms of the sensitivity and coefficient of determination. By the uncertainty assessment, it is found that the uncertainty of resultant powering prediction was smaller than the test uncertainty.